Studi Pemilihan Transportasi Publik di Kota Yogyakarta - Dwi Kunto Nurkukuh (Retii, 2020)
One of the problems in Yogyakarta is the increase in vehicle volume. One solution to reduce the volume of vehicles using private vehicles to public transportation. Public interest in public transportation in the city of Yogyakarta has decreased. The purpose of examining people's preferences in choosing the mode of public transportation in Yogyakarta City. The research method was carried out through a descriptive quantitative approach using the AHP method. Sampling was done by accidental sampling. Public transportation in Yogyakarta City is divided into 2 types, namely online and conventional public transportation modes. From the results of this study it can be seen that the people of Yogyakarta City prefer to use online public transportation modes. The people of the city of Yogyakarta in choosing a mode of public transportation consider the criteria in the following order: safety, comfort, time, then cost. The Online Public Transportation mode is preferred by the people of Yogyakarta City because it meets the criteria of cost (more economical), time (faster), easier to obtain), security (safer), and convenience (more comfortable) compared to conventional public transportation modes. The use of types of public transportation vehicles selected based on the highest order, namely online motorbike taxis, offline motorbike taxis, online car ojek, Trans Yogyakarta buses, pedicab, then conventional taxis.